Role of Vibrational Spectroscopy in Stem Cell Research. Issue 3 (3rd June 2012) - Aksoy Aksoy, Ceren Ceren; Severcan Severcan, Feride Feride
Abstract : Recent researches have mainly displayed the significant role of stem cells in tissue renewal and homeostasis with their unique capacity to develop different cell types. These findings have clarified the importance of stem cells to improve the effectiveness of any cell therapy for regenerative medicine. Identification of purity and differentiation stages of stem cells are the greatest challenges of stem cell biology and regenerative medicine. The existing methods to carefully monitor and characterize the stem cells have some unwanted effects on the properties of stem cells, and these methods also do not provide real-time information about cellular conditions. These challenges enforce the usage of nondestructive, rapid, sensitive, high quality, label-free, cheep, and innovative chemical monitoring methods. In this context, vibrational spectroscopy provides promissing alternative to get new information into the field of stem cell biology for chemical analysis, quantification, and imaging of stem cells. Raman and infrared spectroscopy and imaging can be used as a new complimentary spectroscopic approaches to gain new insight into stem cell reseaches for future therapeutic and regenerative medicines. In this paper, recent developments in applications of vibrational spectroscopy techniques for stem cell characterization and identification are presented.